Fusarium solani and Fusarium moniliforme in coconut leaf rot disease - M. GUNASEKARAN, N. SRINIVASAN and (Indian Phytopathology, 2002)
Two Fusarium species were frequently isolated from coconuts infected with leaf rot disease, along with other species. The role of Fusarium spp. in leaf rot disease of coconut was assessed. F. solani and F. moniliforme var. intermedium [Gibberella fujikuroi var. intermedia] were identified from diseased plants. Pathogenicity was tested by inoculating leaves, which revealed that both species induced the development of symptoms and could be re-isolated from the infected plants.